Educação positiva com mães: um estudo de viabilidade de intervenção remota - Tarazona, Jessica Giovanna Espinoza (2022)
This dissertation was developed and is composed of a scientific text and a study aimed to evaluate the feasibility of the program "Projeto Parceria - Módulo 2" in remote modality. The first study consists of an integrative review of Brazilian and international literature, the objective was to identify and analyze studies the impacts of exposure to intimate partner violence on the mother-child relationship. From the analysis of the 10 articles selected, it was possible to conclude that there are possible damages caused in mother-child relationships by exposure to IPV, with lower quality of the maternal bond, weakening of maternal skills, increased punitive behavior and overprotection, increased of conflicts, parenting practices and damage mother-child relationship in general. Suggesting the need to develop studies that provide knowledge about exposure to IPV and its impacts on the mother-child relationship. Positive parenting is related to parenting practices and their effects, positive parenting practices play an important role in child development. In this context, the second study describes the process of the feasibility of parental program in the remote modality, “Positive education of your children”. For the recruitment of participants, channels such as social media were used. This program has been adapted for the digital platform. Positive changes were observed for some participants as depression, moral behavior, neglect, relaxed discipline, and physical abuse. Most participants rated the intervention as positive, good acceptance criteria, and were satisfied with the program. The intervention appears to be promising and feasible in the remote modality. Some limitations and possibilities for future research are discussed.